Dual Diagnosis of mental illness and acquired brain injury: Making positive changes towards rehabilitation and recovery - Cocks, Errol; Netto, Julie; Bulsara, Caroline; O'Callaghan, Annalise (AST Management Pty Ltd, 2012)
Aim: The aim of this exploratory study was to describe some of the challenges faced by people with dual diagnosis of Acquired Brain Injury (ABI) and Mental Illness (MI); and from these findings make recommendations on service practices and policies required for an effective post discharge rehabilitation and recovery pathway. Methods: This study used in depth interviews of eight individuals and/or their families, and case managers. Qualitative analysis was used to identify key themes. Findings: Participants faced a lack of appropriate supports which reflected a deficiency of expertise in understanding the complex needs of people with ABI and mental illness. Participants were categorized as having ABI or MI leading to lack of engagement in meaningful activities, suitable employment opportunities and a lack of appropriate supports for families .